MICROFINANCE AS A TOOL FOR ECONOMIC EMPOWERMENT OF THE UNDERPRIVILEGED - Erwin; A. Hamid; Mohd Syahrin (Adisam Publisher, 2025)
Microfinance is a financial service aimed at individuals or small businesses that typically do not have access to conventional banking and financial services. It aims to promote economic independence and reduce poverty by providing credit, savings, insurance, and other financial services to small businesses and low- income individuals. These services assist them in starting or expanding their businesses, increasing their income, and gradually improving their standard of living. The research method conducted in this study is the literature research method. The results of the literature review show that microfinance has significant potential in supporting entrepreneurial activities, increasing income, and reducing poverty. Furthermore, microfinance has proven to be effective in enhancing women's economic capacity, giving them access to financial resources that were previously unreachable. However, its effectiveness depends on a number of factors such as programme design, local economic conditions, and the level of financial literacy of the recipients. The research also identified several challenges, including the risk of over-indebtedness and financial instability for borrowers.